Effectiveness and safety of ginkgo biloba preparations in the treatment of Alzheimer's disease: A systematic review and meta-analysis - Li, Dawei; Ma, Jinlong; Wei, Baojian; Gao, Shuang; Lang, Yanmei; Wan, Xueying (Frontiers in Aging Neuroscience, 2023)
Objective: To conduct a meta-analysis of the effectiveness and safety of ginkgo biloba preparations combined with donepezil hydrochloride versus donepezil for the treatment of Alzheimer’s disease (AD). Methods: Three English databases (Cochrane Library, PubMed, EMBASE), and four Chinese databases [the China National Knowledge Infrastructure (CKNI), Chinese Biomedical Literature database (CBM), the Chongqing VIP database, and WANFANG DATA)] were manually searched for literature published from dates of the inception of the databases to December 2022. The randomized controlled trials (RCTs) of ginkgo biloba preparations with donepezil hydrochloride versus donepezil for the treatment of AD were included. Relevant literature was screened, and the data in the included studies were extracted for quality assessment according to the Risk of bias tool. The RevMan 5.3 software was used for meta-analysis. Results: A total of 1642 participants were enrolled in the eighteen RCTs. Of these, 842 were in the experimental group (ginkgo biloba preparations combined with donepezil hydrochloride) and 800 were in the control group (donepezil). The overall methodological quality of the included RCTs is poor due to the high risks of blindness and allocation concealment. The meta-analysis results showed statistically significant differences in several outcomes including Risk Ratio (RR) in change for clinicaleffectiveness rate (1.23, 95% CI 1.13,1.34, P<0.00001), mean difference (MD) in change for Mini-mental State Examination score (3.02, 95% CI 2.14, 3.89, P<0.00001), Activity of Daily Living Scale score (-4.56, 95% CI -5.09, -4.03, P<0.00001), Hasegawa Dementia Scale score ( 2.04, 95% CI 1.74, 2.34, P<0.00001), Montreal Cognitive Assessment score (2.38, 95% CI 0.72, 4.06, P=0.005), between the experimental and control groups. But there is no statistically significant difference in change for adverse reaction (0.91, 95% CI 0.58, 1.42, P=0.69). Conclusion: Kinkgo biloba preparations plus donepezil can improve clinical effectiveness rate and vocabulary memory outcomes. However, more relevant high-quality RCTs are needed in the future to validate these results.